Validity and reliability of the Scoliosis Research Society Questionnaire (SRS-22) in adolescents with idiopathic scoliosis from a national rehabilitation institute - Amaya-Solís, Karen Patricia (2025)
Objective: To Determine the validity and reliability of the Scoliosis Research Society Questionnaire (SRS-22) in Peruvian adolescents with idiopathic scoliosis in a national rehabilitation institute. Materials and methods: Seventy-three adolescents affected by idiopathic scoliosis between 10 and 17 years of age [13.6±1.8), collected through non-probability sampling, were evaluated. Validity based on internal structure was reported through confirmatory factor analysis; reliability by means of Cronbach's Alpha and McDonald's Omega coefficient; and validity based on the relationship with other variables was tested between the SRS-22 with the Short Form Survey Questionnaire (SF-36) and QoL Profile for Spine Deformities (QLPSD). Results: The original model [SRS-22) was found to have adequate evidence of factorial validity with better fit indices (X2 /gL=1.36, CFI=0.962, TLI=0.956, RMSEA=0.07 [0.047-0.091], SRMR=0.122) compared to the short models [SRS-16 and SRS-7). The reliability of the original model was satisfactory for each of the factors, with values above 0.70. Regarding validity based on the relationship with other variables, direct significant relationships were identified between the SRS-22 and SF-36 and QLPSD. Conclusions: The SRS-22 has adequate evidence of validity and reliability for the sample evaluated, requiring further revision of the short versions.